Strictly Conserved Lysine of Prolyl-tRNA Synthetase Editing Domain Facilitates Binding and Positioning of Misacylated tRNA(Pro) - Bartholow, Thomas G. (American Chemical Society, 2014)
[Image: see text] To ensure high fidelity in translation, many aminoacyl-tRNA synthetases, enzymes responsible for attaching specific amino acids to cognate tRNAs, require proof-reading mechanisms. Most bacterial prolyl-tRNA synthetases (ProRSs) misactivate alanine and employ a post-transfer editing mechanism to hydrolyze Ala-tRNA(Pro). This reaction occurs in a second catalytic site (INS) that is distinct from the synthetic active site. The 2′-OH of misacylated tRNA(Pro) and several conserved residues in the Escherichia coli ProRS INS domain are directly involved in Ala-tRNA(Pro) deacylation. Although mutation of the strictly conserved lysine 279 (K279) results in nearly complete loss of post-transfer editing activity, this residue does not directly participate in Ala-tRNA(Pro) hydrolysis. We hypothesized that the role of K279 is to bind the phosphate backbone of the acceptor stem of misacylated tRNA(Pro) and position it in the editing active site. To test this hypothesis, we carried out pK(a), charge neutralization, and free-energy of binding calculations. Site-directed mutagenesis and kinetic studies were performed to verify the computational results. The calculations revealed a considerably higher pK(a) of K279 compared to an isolated lysine and showed that the protonated state of K279 is stabilized by the neighboring acidic residue. However, substitution of this acidic residue with a positively charged residue leads to a significant increase in Ala-tRNA(Pro) hydrolysis, suggesting that enhancement in positive charge density in the vicinity of K279 favors tRNA binding. A charge-swapping experiment and free energy of binding calculations support the conclusion that the positive charge at position 279 is absolutely necessary for tRNA binding in the editing active site.